Use of the Viabahn covered stent for the treatment of venous rupture during interventions of dysfunctional or thrombosed hemodialysis vascular access. Issue 5 (September 2021) - Lee, Chih-Kuo; Hsieh, Ming-Chien; Luo, Chien-Ming; Liao, Min-Tsun; Hsieh, Mu-Yang; Wu, Chih-Cheng
Background: Angioplasty-related vessel rupture is a common complication of interventions. The effect of covered stents to treat venous rupture has been evaluated in smaller series, but should be further evaluated. Objective: To report the immediate outcomes and patency rates of a covered stent to rescue angioplasty-related venous rupture of hemodialysis vascular access. Methods: From January 2013 to December 2018, 113 procedures complicated with vessel ruptures were retrospectively analyzed from a prospectively collected database of 8146 hemodialysis access interventions. The strategies to salvage vessel ruptures were based on the discretion of the treating physicians. Follow-up outcomes were obtained via review of the angiographic images, procedural notes, and medical and dialysis records within 12 months after the index procedures. Results: A total of 52 vessel ruptures (21 fistulas, 31 grafts) salvaged by using Viabahn covered stents were enrolled. Vessel ruptures developed in 28 (53.8%) thrombectomy procedures. Device success was achieved in all procedures (100%) and clinical success was achieved in 50 (96.2%). The primary patency of the stent area was 66.0% at 6 months and 50.0% at 12 months. The primary patency of the entire access circuit was 27.4% at 6 months and 16.0% at 12 months. The most common cause of access circuit primary patency loss was thrombotic occlusion for graft accesses and restenosis at stent area for native accesses. Eleven vascular accesses were abandoned within 12 months after vessel ruptures, and the secondary patency rate of the entire access circuit was 78.0% at 12 months. Conclusions: Treatment of angioplasty-induced vessel rupture of hemodialysis vascular accesses by using Viabahn covered stents has good immediate outcomes and patency results at the stent area. Nonetheless, the patency rate of entire access circuit was still below the threshold recommended by guidelines.